Derivation of Met-Ocean Conditions for the Simulation of Floating Wind Turbines: a European case study. Issue 1 (1st December 2022) - Papi, F.; Perignon, Y.; Bianchini, A.
Abstract: Offshore wind turbines are subject not only to varying wind conditions during their lifetime, but also sea conditions. Therefore, in addition to wind speed, other sea-related quantities need to be considered to characterize a specific installation site. International standards suggest that, at a minimum, significant wave height, peak spectral period and wind/wave misalignment must be considered. In order to have a statistically significant description of the potential installation site, the long-term distributions of the three environmental variables must be determined. In this context, the objectives of the present work are twofold: firstly, to demonstrate the procedure trough which environmental conditions including wind and wave information can be derived using open-source tools. Secondly, an exemplary dataset is provided. The dataset is used both do demonstrate the procedure and provided as a ready-made example for use in future studies. The provided dataset is used in the EU-funded Horizon 2020 project FLOATECH.